HOW STATELESS PERSON BECOMES A CHINESE CITIZEN - Zhengrong, Luo (Наукові записки. Серія: Право, 2023)
This article is part of the aforementioned recent international interest in the issue of statelessness, more specifically as a result of a research project commissioned by the UNHCR office in China in 2016. As the most populous country and the second largest economy in the world. Does China have a statelessness problem? How does China feel about it? Is there a gap between China’s actions and international law, especially human rights requirements? These questions have not been studied much. Therefore, it makes sense and even needs to be examined more closely. The article is devoted to the protection of stateless persons in China, which has two levels of objectives: first, to examine whether China has a legal and policy framework to prevent and/or reduce statelessness; second, while there are stateless cases, to study how stateless persons are treated in China. For both missions, this study will examine China’s actions in light of international law, particularly international human rights standards, including the 1954 Convention relating to the Status of Stateless Persons, the 1961 Convention on the Reduction of Statelessness, and all relevant international human rights treaties. and UN instruments. This article analyzes the legal basis and requirements for obtaining Chinese citizenship and citizenship certificates, including the Constitution, the Nationality Law, the Law on the Management of Exit and Entry, the Law on the Resident Identity Card, the Household Registration Ordinance and Temporary Provision on Residence Permit and other relevant laws and regulations. The article examines possible situations where people are de jure or de facto stateless in China and attempts to identify the main obstacles and challenges for possible resolution. The article analyzes the problems of statelessness in China from the point of view of international law and indicates China’s obligations regarding statelessness in accordance with the international human rights system.